2022
DOI: 10.34133/2022/9816536
|View full text |Cite
|
Sign up to set email alerts
|

Global Terrestrial Ecosystem Carbon Flux Inferred from TanSat XCO 2 Retrievals

Abstract: TanSat is China’s first greenhouse gases observing satellite. In recent years, substantial progresses have been achieved on retrieving column-averaged CO2 dry air mole fraction (XCO2). However, relatively few attempts have been made to estimate terrestrial net ecosystem exchange (NEE) using TanSat XCO2 retrievals. In this study, based on the GEOS-Chem 4D-Var data assimilation system, we infer the global NEE from April 2017 to March 2018 using TanSat XCO2. The inversion estimates global NEE at −3.46 PgC yr-1, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Two studies (Wang, Jiang, et al, 2022; Yang, Liu, Feng, et al, 2021) have used the retrieval products for 15 months (Yang, Liu, Boesch, et al, 2021) released by the TanSat group to estimate the global and regional land carbon sink by atmospheric inversion. The inversion estimates of global land carbon flux using TanSat XCO 2 retrievals are generally consistent with the inversions using OCO‐2 retrievals.…”
Section: Inversion Estimates Of China's Land Carbon Sink Using Satell...mentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies (Wang, Jiang, et al, 2022; Yang, Liu, Feng, et al, 2021) have used the retrieval products for 15 months (Yang, Liu, Boesch, et al, 2021) released by the TanSat group to estimate the global and regional land carbon sink by atmospheric inversion. The inversion estimates of global land carbon flux using TanSat XCO 2 retrievals are generally consistent with the inversions using OCO‐2 retrievals.…”
Section: Inversion Estimates Of China's Land Carbon Sink Using Satell...mentioning
confidence: 99%
“…Two studies (Wang, Jiang, et al, 2022;Yang, Liu, Feng, et al, 2021) have used the retrieval products for 15 months (Yang, Liu, Boesch, et al, 2021) released by the TanSat group to estimate the global and regional land carbon sink by atmospheric inversion.…”
Section: Inver S I On E S Timate S Of China' S L and C Arbon S Ink Us...mentioning
confidence: 99%
See 1 more Smart Citation
“…In November 2019, the GF-7 satellite was launched with two linear system laser altimeters, which opened the exploration of full-waveform large-footprint laser altimetry in China [17][18][19][20]. Recently, the Terrestrial Ecosystem Carbon Inventory Satellite, dedicated to forest resource surveys, has been launched, carrying a five-beam lidar load for acquiring high-precision three-dimensional structures of forests at large footprints [21,22]. To verify the performance of the laser altimeter system, the National Forestry and Grassland Administration, together with scientific research institutes, carried out the development and flight testing of an airborne large-footprint laser altimeter system.…”
Section: Introductionmentioning
confidence: 99%
“…Remotesensing-based CO 2 measurements provide global coverage with high spatial resolutions (Baker et al, 2010). Many studies have estimated regional carbon sources and sinks using column averaged dry air mole fractions of CO 2 (XCO 2 ) from GOSAT and OCO-2 satellites (Baker et al, 2010;Basu et al, 2013;Byrne et al, 2020;Chevallier et al, 2014Chevallier et al, , 2019Crowell et al, 2019;Deng et al, 2014;Houweling et al, 2015;Jiang et al, 2021;Wang et al, 2018Wang et al, , 2019Wang et al, , 2022, boosting the possibility of better constraining the carbon cycle at finer spatial scale (Byrne et al, 2019). The GOSAT intercomparison study from Houweling et al (2015) found that robust estimates could be obtained at large global scale, but at the TRANSCOM regions, the different inversions differed significantly.…”
mentioning
confidence: 99%